2012
DOI: 10.1186/2193-1801-1-73
|View full text |Cite
|
Sign up to set email alerts
|

Chitinolytic assay of indigenous Trichoderma isolates collected from different geographical locations of Chhattisgarh in Central India

Abstract: Chitin is the second most abundant polymer in nature after cellulose and plays a major role in fungal cell walls. As a producer of variety of chitinase enzymes Trichoderma has become an important means of biological control of fungal diseases. A simple and sensitive method based on the use of basal medium with colloidal chitin as sole carbon source supplemented with Bromo cresol purple (pH indicator dye) is proposed to evaluate large populations of Trichoderma for chitinase activity. The soluble substrate with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 36 publications
2
100
0
5
Order By: Relevance
“…Agrawal and Kotasthane (2012) indicated that this Trichoderma species presented chitinolytic activity with colloidal chitin supplementation higher than that of T. harzianum, T. viride, T. virens and T. citirinoviride, because T. aureoviride has high affinity to colloidal chitin. Agrawal and Kotasthane (2012) indicated that this Trichoderma species presented chitinolytic activity with colloidal chitin supplementation higher than that of T. harzianum, T. viride, T. virens and T. citirinoviride, because T. aureoviride has high affinity to colloidal chitin.…”
Section: Discussionmentioning
confidence: 91%
“…Agrawal and Kotasthane (2012) indicated that this Trichoderma species presented chitinolytic activity with colloidal chitin supplementation higher than that of T. harzianum, T. viride, T. virens and T. citirinoviride, because T. aureoviride has high affinity to colloidal chitin. Agrawal and Kotasthane (2012) indicated that this Trichoderma species presented chitinolytic activity with colloidal chitin supplementation higher than that of T. harzianum, T. viride, T. virens and T. citirinoviride, because T. aureoviride has high affinity to colloidal chitin.…”
Section: Discussionmentioning
confidence: 91%
“…Based on the previous in vitro antagonistic assay, a total of 10 Trichoderma strains Trichoderma asperellum CCTCC-SBW0102 (T3), T. aureoviride CCTCC-SBW0005 (T9), T. harzianum CCTCC-SBW0101 (T11), T. asperellum CCTCC-SBW0109 (T12), T. atroviride CCTCC-SBW0016 (T21), T. asperellum CCTCC-SBW0052 (T43), T. asperellum CCTCC-SBW0091 (T44), T. tawa (T64), T. harzianum CCTCC-RW0024 (T72), and T. harzianum CCTCC-SBW0181 (T88) were selected for the preliminary enzyme assay 4143 . The percentage of the enzyme activity was calculated using the following formula as Hydrolysis capacity (%) = Diameter of clear zone (cm)/Diameter of Trichoderma colony (cm).…”
Section: Methodsmentioning
confidence: 99%
“…Chitin is a polymer of chitobiose, which consists of two NAGA residues bound to each other by β-1, 4 glycosidic linkage. The active groups present in NAGA molecules are hydroxyl, carbonyl, and imine groups at which anionic dye like BCP is bind and generates color-bound complex (yellow) [2] (pH 4.7) when Trichoderma inoculated in colloidal chitin media having BCP resulted in the formation of chitin into N-acetylglucosamine causing change in pH to more alkalinity and also change in color of indicator dye (BCP) from yellow to purple zone where the chitin got utilized. ) are detected by BCP in the Arrhenius model.…”
Section: Discussionmentioning
confidence: 99%
“…Genus Trichoderma and efficient biocontrol strain are being industrialized as effective biological fungicides, and their biocontrol mechanism of biological control involves the role of secondary metabolites with prospective applications as new antibiotics [1,2]. They produce many antifungal enzymes including chitin-degrading enzymes which used economically as a basis of these kind of proteins.…”
Section: Introductionmentioning
confidence: 99%